Synthesis of ammonium iron (II) sulfate-doped nano-TiO2 photocatalyst for the removal of 4-chlorophenol under visible light irradiation - Villaluz, Finella Jianna A.; De Luna, Mark Daniel G.; Lu, Ming-Chun (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
4-Chlorophenol (4-CP) is listed as a primary water pollutant in the U.S. EPA for its potential as a carcinogen and mutagen to mammals as well as to aquatic life. In this study, the removal of this pollutant through visible-light photocatalysis was dealt with using the synthesized(NH,)2Fe(SO4)2-doped nano-TiO2photocatalyst.The effects of varying synthesis parameters namely amount of dopant, calcination temperature, and amount of acid were examined as well as the effects of photocatalyst dosage, pH, and initial 4-CP concentration as operating parameters. Sol-gel method was used to effectively synthesize the photocatalysts, which were subsequently characterized by Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDX), X-ray Diffraction (XRD), Ultraviolet-visible Diffuse Reflectance (UV-vis DRS), X-ray Photoelectron Spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) Analyses. Through the use of High Performance Liquid Chromatography(HPLC) analysis,99.20% of 10 ppm 4-CP mixed with 0.40 g/L synthesized photocatalyst in a solution with a pH of 7.0 was successfully removed after 3 h at the specified synthesis parameter conditions of dopant amount (0.10 mol% of 0.20 M (NH4)2Fe(SO4)2), amount of nitric acid (0.05 vol% of 65% HNO3/Ti(OBu)4), and calcination temperature (400°C). It was also found out that the photocatalyst can be reused 4 times or more at the same experimental conditions. Lastly, the Langmuir-Hinshelwood model favorably describes the rate of reaction of 4- CP with the calculated values for the rate constant, kLH, equivalent to 0.429 min and Langmuir adsorption constant, KL, equal to 2.326 ppm-1.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Chlorophenols; Water -- Purification -- Photocatalysis